Dietary zinc alters the microbiota and decreases resistance to Clostridium difficile infection - Zackular, Joseph P; Moore, Jessica L; Jordan, Ashley T; Juttukonda, Lillian J; Noto, Michael J; Nicholson, Maribeth R; Crews, Jonathan D; Semler, Matthew W; Zhang, Yaofang; Ware, Lorraine B; Washington, M Kay; Chazin, Walter J; et al. (Nature medicine, 2016)
Dietary zinc supplements are in common use, but their effect on infection is unclear. New findings now show that excess dietary zinc reduces the diversity of the gut microbiota and increases the susceptibility of antibiotic-treated mice to Clostridium difficile infection. Clostridium difficile is the most commonly reported nosocomial pathogen in the United States and is an urgent public health concern worldwide 1 . Over the past decade, incidence, severity and costs associated with C. difficile infection (CDI) have increased dramatically 2 . CDI is most commonly initiated by antibiotic-mediated disruption of the gut microbiota; however, non-antibiotic-associated CDI cases are well documented and on the rise 3 , 4 . This suggests that unexplored environmental, nutrient and host factors probably influence CDI. Here we show that excess dietary zinc (Zn) substantially alters the gut microbiota and, in turn, reduces the minimum amount of antibiotics needed to confer susceptibility to CDI. In mice colonized with C. difficile , excess dietary Zn severely exacerbated C. difficile– associated disease by increasing toxin activity and altering the host immune response. In addition, we show that the Zn-binding S100 protein calprotectin has antimicrobial effects against C. difficile and is an essential component of the innate immune response to CDI. Taken together, these data suggest that nutrient Zn levels have a key role in determining susceptibility to CDI and severity of disease, and that calprotectin-mediated metal limitation is an important factor in the host immune response to C. difficile .